2017
DOI: 10.1038/s41467-017-00986-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial intracellular adenosine via adenosine kinase epigenetically modulates vascular inflammation

Abstract: The molecular mechanisms underlying vascular inflammation and associated inflammatory vascular diseases are not well defined. Here we show that endothelial intracellular adenosine and its key regulator adenosine kinase (ADK) play important roles in vascular inflammation. Pro-inflammatory stimuli lead to endothelial inflammation by increasing endothelial ADK expression, reducing the level of intracellular adenosine in endothelial cells, and activating the transmethylation pathway through increasing the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…ADK-L is reported to affect epigenetic remodeling [19,20] and is thought to preferentially function as a regulator of methyltransferase action through clearance of adenosine [17,21]. On the other hand, ADK-S regulates extracellular adenosine concentration to activate various adenosine receptor subtypes and affects angiogenesis [22], inflammation [20], and immune suppression [23]. These functions of ADK isoforms strongly support a differential role for ADK-L versus ADK-S in cancer.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…ADK-L is reported to affect epigenetic remodeling [19,20] and is thought to preferentially function as a regulator of methyltransferase action through clearance of adenosine [17,21]. On the other hand, ADK-S regulates extracellular adenosine concentration to activate various adenosine receptor subtypes and affects angiogenesis [22], inflammation [20], and immune suppression [23]. These functions of ADK isoforms strongly support a differential role for ADK-L versus ADK-S in cancer.…”
Section: Introductionmentioning
confidence: 96%
“…This differential expression suggests a distinctive role for ADK-L (versus ADK-S) on proliferation and differentiation -two major nuclear activities that are tightly linked to cancer pathology [18]. ADK-L is reported to affect epigenetic remodeling [19,20] and is thought to preferentially function as a regulator of methyltransferase action through clearance of adenosine [17,21]. On the other hand, ADK-S regulates extracellular adenosine concentration to activate various adenosine receptor subtypes and affects angiogenesis [22], inflammation [20], and immune suppression [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic reperfusion injury, characterized as myocardial damage and unstoppable cell death . Numerous studies have identified various pathological factors involved in the pathological process, including mitochondrial dysfunction, inflammatory response, endoplasmic reticulum stress, and oxidative stress . Despite extensive efforts having been put into the research of myocardial infarction and ischemic reperfusion injury, there still existed little effective treatment and intervention target …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, endothelial cells play an essential role in maintaining the blood brain barrier, while endothelial dysfunction contributes to vascular disease and stroke (Roquer et al, 2009). Inflammation and apoptosis can induce endothelial damage after stroke (Suzuki and Urano, 2011;Xu et al, 2017). Our results showed that NLRP3 in the endothelial cells after SAH could be mitigated by hydrogen inhalation.…”
Section: Discussionmentioning
confidence: 71%